The Effect of Business Environment on The Performance of SMIs in The Food and Beverage Sector through Marketplace Adoption as A Mediating Variable - Yusti Mauriska Choirunnisa; Djoko Koestiono; Fitria Dina Riana; Abdul Wahib Muhaimin; Dwi Retno Andriani (HABITAT, 2023)
This research was conducted at SMIs which was seen from its growth that SMIs had the opportunity to develop in this city. This study aims to describe and analyze the effect of entrepreneurial orientation and the role of government through marketplace adoption on company performance. This study used non-probability sampling with a purposive sampling technique to the owners/managers of companies totaling 50 respondents. This research method is SEM-PLS (Structural Equation Model - Partial Least Square) and uses Warp PLS 7.0 software. The results of the study show that: (1) Marketplace adoption has a positive effect on the SMI performance; (2) Entrepreneurial orientation has a positive and significant effect on marketplace adoption and SMI performance; (3) Role of government has a positive and highly significant effect on marketplace adoption and SMI performance; (4) Adoption of marketplace has a positive and highly significant effect on SMI performance; (5) For the indirect effect, entrepreneurial orientation to company performance through marketplace adoption has a significant positive effect and role of government to company performance through marketplace adoption has a significant positive effect.